KOMBINASI BUMBU DAN ASAP CAIR DALAM MEMINIMALKAN PEMBENTUKAN HISTAMIN PADA IKAN KEMBUNG PEREMPUAN (Rastrelliger neglectus) ASAP [Combination of Spice and Liquid Smoke in Minimizing Histamine Formation in the Smoked Mackerel (Rastrelliger neglectus)] - Meta Mahendradatta; Abu Bakar Tawali (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2006)
Four spices (clove, cinnamon, tamarind and ginger) were combined and applied to produce smoked female mackerel. The use of liquid smoke was compared with redistilled liquid smoke. The result showed that there was lower histamine content in smoked fish treated with spices after the use of liquid smoke and redistilled liquid smoke at (1.00 – 1.20mg/100g) compared with the raw material (1.55mg/100g). Histamine content in all treatments increased during storage from 0.96 – 1.13 mg/100g to 6.40 -20.29mg/100g. The phenol content decreased during storage from 2.19% - 2.44% to 0.72% - 0.84%. Using of liquid smoke in combination with spice as well as without spice,resulted in decreasing of the free fatty acid (FFA) content until 20 days of storage then increased, whereas using redistilled liquid smoke, resulted decreased of FFA during 10 days storage before increased. Total psychrophilic microbe was not detectable at 0 and 10 days storage but then increased at 20 and 30 days storage to 6.5x103 – 10.1x103cfu/ml and 7.5x103 – 15.5x103cfu/ml, respectively. Overall, combination between clove-cinnamon and liquid smoke which was applied to female mackerel showed the best result i.e.: lower histamine content, lower FFA, lower total psychrophilic microbe and lower phenol content than other treatments. The acceptability of smoked fish treated with clove-cinnamon and liquid smoke after 30 days storage showed higher value than other treatments. Key words: histamine formation, redistilled liquid smoke, spices, short-bodied mackerel